Electronic devices and circuits - Hassul, Michael (Prentice Hall, 1997)
This book addresses concerns over reader attraction to the electronics curricula. To combat the high levels of reader intimidation and frustration caused by many electronics books, these authors present material in small, manageable bites, using everyday metaphors to explain device behavior and using humor to make points.